Sub-100 ps coincidence time resolution for positron emission tomography with LSO:Ce codoped with Ca. (21st June 2015) - Nemallapudi, Mythra Varun; Gundacker, Stefan; Lecoq, Paul; Auffray, Etiennette; Ferri, Alessandro; Gola, Alberto; Piemonte, Claudio
Abstract The coincidence time resolution (CTR) becomes a key parameter of 511keV gamma detection in time of flight positron emission tomography (TOF-PET). This is because additional information obtained through timing leads to a better noise suppression and therefore a better signal to noise ratio in the reconstructed image. In this paper we present the results of CTR measurements on two different SiPM technologies from FBK coupled to LSO:Ce codoped 0.4%Ca crystals. We compare the measurements performed at two separate test setups, i.e. at CERN and at FBK, showing that the obtained results agree within a few percent. We achieve a best CTR value of 85 ± 4 ps FWHM for 2 × 2 × 3 mm3 LSO:Ce codoped 0.4%Ca crystals, thus breaking the 100 ps barrier with scintillators similar to LSO:Ce or LYSO:Ce. We also demonstrate that a CTR of 140 ± 5 ps can be achieved for longer 2 × 2 × 20 mm3 crystals, which can readily be implemented in the current generation PET systems to achieve the desired increase in the signal to noise ratio.